Remark on the Lebesgue constant in the Rogosinski Kernel - Dzyadyk, V. K.; Shevchuk, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For every n, we compute the Lebesgue constant of Rogosinski kernel with any preassigned accuracy.